Tocopherols: Structure, Distribution, Biosynthesis, Genetics and Breeding Aspects in Plants - Shilpa Gupta; Manjeet Kaur Sangha; Sucheta Sharma (New Innovations in Chemistry and Biochemistry Vol. 8, 2022)
Vitamin E comprised tocopherol derivatives in four different forms i.e. \(α\), \(β\), \(γ\), and \(δ\). \(α\)-tocopherol is the prevalent form in photosynthetic tissues whereas, in seeds, it is \(γ\)-tocopherol. The total tocopherol content, their types, composition, and distribution vary in different plant tissues and under different developmental stages. Earlier, plastids were considered to be the unique subcellular localization of tocopherols, but recently their presence has also been suggested in seed lipid bodies, vacuoles, and nuclei of mesophyll cells. Tocopherol biosynthesis involves shikimate and methylerythritol phosphate (MEP) pathways, however, under limiting conditions, the MEP pathway may be switched to phytol recycling pathway during chlorophyll degradation. Tocopherols are involved in multiple functions in plant cells viz. scavenging free radicals, maintaining membrane integrity and stability; physiological regulation of enzyme activity, cellular/retrograde signaling, and gene expression. For breeding, trait variability is the prerequisite. Several studies revealed molecular and genetic bases underlying the variation in content and composition of tocopherol. The characterization of the identified QTLs in different oilseed crops may facilitate the use of high \(α\)-tocopherol alleles from wild varieties in different breeding programmes for the generation of high tocopherol genotypes that could ultimately pave a way for edible oil quality improvement of different oilseed crops. Keeping all these aspects in mind, the study was carried out with following objectives: 1. Structural and distributional aspects of tocopherols in plants 2. Biosynthesis, genetics and functions of tocopherols 3. Tocopherol breeding in oilseeds.